Development of A School Website Using The Laravel Framework as A Platform for Information and Promotion - Ferri Satya Nugraha; Bagus Sudirman; Ahmad Ashifuddin Aqham (CV. Publikasi Indonesia, 2026)
The development of information technology in the digital era requires educational institutions to adapt in the dissemination of information and promotion. PKBM Tunas Harapan Jaya currently still relies on conventional media such as brochures and banners that have limited reach and relatively high costs. This causes the dissemination of information to the wider community and prospective students to be less effective and efficient. This study aims to design and build a school website based on the Laravel framework as a digital information and promotion medium for PKBM Tunas Harapan Jaya. The research method used was Research and Development with a Prototype system development model. The development stages include needs analysis, system design, database design using MySQL, interface implementation, and system testing. The result of this study is a web-based information system that presents the school profile, educational programs, activity galleries, the latest news, and registration information. This website is designed to be easily managed by the school and easily accessible to the general public. With this website, it is hoped that the promotional reach of PKBM Tunas Harapan Jaya will be wider, information delivery will be more real-time, and the institution's credibility image in the eyes of the public.